Review paperAssociation of cardiomyopathy and celiac disease: an almost diffuse but still less know entity. A review - Curione, Mario; Barbato, Maria; Cugini, Pietro; Amato, Silvia; Da Ros, Silvia; Di Bona, Simonetta (Archives of Medical Science, 2008)
Introduction: This study is a systematic revision of scientific articles regarding the epidemiological, clinical and therapeutic aspects of cardiomyopathy associated with celiac disease. Material and methods: 1193 adult cases of cardiomyopathy and 15890 clinically healthy control subjects have been scrutinized. Results: The prevalence of celiac disease in cardiomyopathy patients was found higher vs control (3.36 vs. 0.425%, P=0.004). The risk of association was 2-3 times higher than expected. Mean age a 42 years ejection fraction was 25%. A gluten free diet induced an improvement in cardiac performance. Conclusions: In patients with cardiomyopaty may be the real risk of a concomitant celiac disease. The study protocol is not able to provide inferences on the cause-effect relationship existing between two diseases. Gluten free diet can improve cardiac performance in patients with this association. In patients with cardiomyopathy, an appropriate screening of celiac disease should be routinely performed.